Randomized double-blind clinical trial evaluation of bone healing after third molar surgery with the use of leukocyte- and platelet-rich fibrin. Issue 8 (August 2019) - Ritto, F.G.; Pimentel, T.; Canellas, J.V.S.; Junger, B.; Cruz, M.; Medeiros, P.J.
Abstract: The objective of this study was to evaluate the use of leukocyte- and platelet-rich fibrin (L-PRF) in bone healing after mandibular third molar extraction. In this prospective, double-blind, split-mouth study, 34 extractions were performed. On one side, the socket was sutured primarily (control side); on the other side, L-PRF was inserted before suturing. The patients were assessed for postoperative bone regeneration, pain and soft tissue healing. The primary outcome was bone regeneration, which was performed through tomographic evaluation in the immediate postoperative period and 3 months after the procedure. The ITK-SNAP software was used for image evaluation by the intensity of grey of each voxel. Pain was analysed using a visual analogue scale (VAS), and soft tissue healing was analysed both based on the modified healing index of Landry et al., and by comparing pre- and postoperative periodontal probing at the distal of the lower second molar. The application of L-PRF improved bone density, which was higher in test group ( p = 0.007). There was no statistical difference related to pain or soft tissue between the groups ( p > 0.05). There was evidence for improved bone healing in response to L-PRF. However, to better understand the effect of L-PRF more clinical trials with larger samples are necessary.